2020
DOI: 10.1111/voxs.12550
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood grouping discrepancies in the donor population

Abstract: Background and Objectives ABO discrepancies occur when the reactions in forward grouping are not corroborative to those in the reverse grouping due to weak subgroups of A and/or B, missing or weak ABO antibodies or unexpected alloantibodies. We aimed to determine the prevalence of ABO discrepancies in our donor population and to know the causes by using a standard classification. Materials and Methods It was a retrospective study on donor samples. For all the discrepant samples, the ABO and RhD grouping was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
(24 reference statements)
0
6
1
1
Order By: Relevance
“…Similar studies done by other authors from different parts of our country ( Table 3 ) have shown that the prevalence of ABO discrepancy ranges from 0.02 to 0.064%. 1 2 4 8 We observed a little higher prevalence rate of ABO discrepancy in comparison to the other studies. Genetic diversity along with a demographic variation of the population in this part of the country could be a possible explanation of the different prevalence rate of ABO discrepancy.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…Similar studies done by other authors from different parts of our country ( Table 3 ) have shown that the prevalence of ABO discrepancy ranges from 0.02 to 0.064%. 1 2 4 8 We observed a little higher prevalence rate of ABO discrepancy in comparison to the other studies. Genetic diversity along with a demographic variation of the population in this part of the country could be a possible explanation of the different prevalence rate of ABO discrepancy.…”
Section: Discussioncontrasting
confidence: 69%
“…A recent study done by Jain et al and a study by Sharma et al observed that type I ABO discrepancy accounted for the predominant type of ABO blood group discrepancy with a percentage frequency of 35.5 and 58.8%, respectively. 4 8 Moreover, both the studies found that weak or low avidity anti-B antibody is the most common cause of type I ABO blood group discrepancy. The changes of ABO isoagglutinin levels related to age, immunodeficiency conditions, and other clinical conditions like post-hematopoietic stem cell transplant are few possible causes of weak or missing reactivity of antibodies in the reverse grouping.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations